Zebrafish Ecoflex System - Siti Zaleha, Raduan; Muhammad Hamdi, Mahmood; Qamar Uddin, Ahmed; Muhammad Salahuddin, Haris; Awis Sukarne, Mohmad Sabere; Saiful Bahari, Hj Mohd Yusoff (2025)
Zebrafish EcoFlex System is a smart, modular aquaria innovation designed to support advanced biomedical research using zebrafish, a model organism with high genetic similarity to the human brain. Since zebrafish behavior is highly sensitive to environmental conditions, EcoFlex provides a stable and enriched aquatic environment through its hydrodynamic tank design, precise water quality control, and integrated live-feed modules. These include artemia shrimp, which enhance natural foraging behavior and maintain tank cleanliness, and astaxanthin-rich algae, a valuable antioxidant widely used in health and cosmetic products. In addition to improving zebrafish welfare and supporting ethical research aligned with the 3R principles, the system introduces entrepreneurship potential through the cultivation and commercialization of shrimp and algae. Affordable, scalable, and sustainable, EcoFlex represents a forward-thinking solution that combines scientific advancement, environmental responsibility, and economic opportunity.